PENYULUHAN PEMBUATAN KERIPIK SUKUN DI DESA SUNGAI BAKAR KECAMATAN BAJUIN KABUPATEN TANAH LAUT - Wasdiyanta; Ahmad Baparki; Rohansyah; Marisandy (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Implementation of community service is carried out through outreach activities to community groups in Sungai Bakar Village using direct participation techniques, by providing guidance on how to make breadfruit chips, the materials and tools used and where the processed breadfruit chips can be marketed. Provides an understanding of the calculation of costs, receipts and income from the breadfruit chips business.